Kajian Kelayakan Rencana Lokasi Baru Tempat Pemrosesan Akhir (TPA) Sampah Di Kelurahan Muara Fajar Kota Pekanbaru - Natalina, Riani; Asmura, Jecky; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pekanbaru City has already had a location of operational final processing of waste in Muara Fajar Village. The operational condition and facilities of landfill in the final stages of capacities, and expansion of the area is difficult resulted in landfill no longer feasible, so it requires a new location as landfill replacement. The new location plans at village of Muara Fajar require a feasibility study with the technical standards prevailing in Indonesia. The volume of waste transported to landfill from 2016 to 2025 is estimated to reach 2,215,951 tons and service life at a new location be able to accommodate waste for 4 years and 5 months. The environmental conditions that need to be considered is slope of 15% to 25%, and existence of groundwater at the valleys at a depth of 0,2 meters to 1,5 meters. Based on Indonesian National Standard (SNI) 03-3241-1994 with scoring analysis landfill is medium worthy.Keywords: new location plans of landfill, Muara Fajar Village, volume of waste, SNI 03-3241-1994/